Preterm Birth: A Prominent Risk Factor for Low Apgar Scores - Svenvik, Maria (Biomed Res Int, 2015)
Objective. To determine predictive risk factors for Apgar scores < 7 at 5 minutes at two hospitals providing tertiary care and secondary care, respectively. Methods. A retrospective registry cohort study of 21126 births (2006–2010) using data from digital medical records. Risk factors were analyzed by logistic regression analyses. Results.  AS(5min⁡) < 7 was multivariately associated with the following: preterm birth; gestational week 32 + 0–36 + 6, OR = 3.9 (95% CI 2.9–5.3); week 28 + 0–31 + 6, OR = 8 (5–12); week < 28 + 0, OR = 15 (8–29); postterm birth, OR = 2.0 (1.7–2.3); multiple pregnancy, OR = 3.53 (1.79–6.96); previous cesarean section, OR = 3.67 (2.31–5.81); BMI 25–29, OR = 1.30 (1.09–1.55); BMI ≥ 30  OR = 1.70 (1.20–2.41); nonnormal CTG at admission, OR = 1.98 (1.48–2.66). ≥1-para was associated with a decreased risk for AS(5min⁡) < 7, OR = 0.34 (0.25–0.47). In the univariate logistic regression analysis AS(5min⁡) < 7 was associated with tertiary level care, OR = 1.48 (1.17–1.87); however, in the multivariate analysis there was no significant difference. Conclusion. A number of partially preventable risk factors were identified, preterm birth being the most evident. Further, no significant difference between the two hospital levels regarding the risk for low Apgar scores was detected.